Porcine Dermal Xenograft as Augmentation in the Treatment of Large Rotator Cuff Tears: Clinical and Magnetic Resonance Results at 2-Year Follow-Up - Castagna, Alessandro; Cesari, Eugenio; Di Matteo, Berardo; Osimani, Marcello; Garofalo, Raffaele; Kon, Elizaveta; Marcacci, Maurilio; Chillemi, Claudio (Joints, 2018)
Purpose The aim of the present retrospective study is to describe the results obtained at 2-year follow-up by using a porcine dermis-derived collagen membrane implanted as augmentation to treat large rotator cuff tears.Methods Thirty-five patients in total were included according to the following criteria: large or massive rotator cuff tear, confirmed during surgery, measuring between 3 and 5 cm in width and stage 1 to 2 fatty infiltration documented at magnetic resonance imaging (MRI). Patients underwent arthroscopic repair of the cuff augmented by the implantation of a porcine dermal collagen membrane. Patients were evaluated up to 24 months after surgery by the Constant score and MRI imaging to assess functional outcomes and re-tear rate. The results obtained were compared to those of a matched cohort of 35 patients operated by arthroscopic repair alone by the same surgical team.Results The application of the porcine membrane proved to be safe without scaffold-related adverse events documented. A statistically significant difference in the Constant score in favor of the treatment group was documented at the final evaluation (p = 0.036). Furthermore, a subgroup analysis revealed that patients treated by augmentation and presenting re-tear at MRI showed a significantly higher functional outcome compared with control patients with MRI evidence of re-tear (p = 0.0136).Conclusion Arthroscopic repair augmented by porcine dermal xenograft for the treatment of chronic and retracted rotator cuff tears with low-grade fatty degeneration proved to be safe and also effective, with higher functional score compared with the arthroscopic repair alone.Level of Evidence This is a Level III, retrospective cohort study.
Keywords: rotator cuff; massive tear; scaffold; dermal collagen membrane; augmentation